2011
DOI: 10.1029/2011ja017094
|View full text |Cite
|
Sign up to set email alerts
|

Fast earthward flows, electron cyclotron harmonic waves, and diffuse auroras: Conjunctive observations and a synthesized scenario

Abstract: [1] We present in this paper multi-instrumental observations and analyses of fast earthward flows, electrostatic electron cyclotron harmonic (ECH) waves, and diffuse auroras, during 8-9 UT on February 5, 2009. The event began with a series of fast earthward flows detected on mid-tail probe THEMIS-C. Subsequently, magnetic dipolarizations and strong ECH wave intensifications were observed on THEMIS-D/E probes at L $ 11 in the equatorial plasma sheet. Concurrently, Ground optical instruments detected diffuse aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 68 publications
1
60
0
Order By: Relevance
“…ECH waves, which do not play a significant role in the formation of the diffuse aurora at low L * [ Thorne et al , 2010], may thus ultimately play an important role at higher values of L *. Indeed, a recent case study involving conjugate ground and space measurements suggests that ECH waves can be the dominant driver of the diffuse aurora in the outer magnetosphere [ Liang et al , 2011; Ni et al , 2012].…”
Section: Discussionmentioning
confidence: 99%
“…ECH waves, which do not play a significant role in the formation of the diffuse aurora at low L * [ Thorne et al , 2010], may thus ultimately play an important role at higher values of L *. Indeed, a recent case study involving conjugate ground and space measurements suggests that ECH waves can be the dominant driver of the diffuse aurora in the outer magnetosphere [ Liang et al , 2011; Ni et al , 2012].…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that use of T01s for chorusinduced electron scattering produces the largest precipitation electron flux, then use of T96 and T04s, and use of T01 gives the weakest precipitation flux due to the smallest degree of loss cone filling. Following the approach by Steele and McEwen (1990) and Liang et al (2011), we have further performed a Maxwellian-type fitting to the precipitation electron differential number flux to roughly estimate the total energy flux and characteristic energy of precipitating electrons. We have obtained a total precipitation electron energy flux of ∼0.08 erg cm −2 s −1 with a characteristic energy of ∼1.9 keV for use of T01, a total precipitation electron energy flux of ∼0.15 erg cm −2 s −1 with a characteristic energy of ∼1 keV for use of T96 and T04s, and a total precipitation electron energy flux of ∼0.6 erg cm −2 s −1 with a characteristic energy of ∼800 eV for use of T01s.…”
Section: Resonant Scattering By Dayside Chorus and Resultant Loss Conmentioning
confidence: 99%
“…Recent studies suggest that diffuse auroras observed on the nightside are predominantly produced by the chorus waves in the inner (L < 8) magnetosphere and by the ECH waves in the outer (L > 8) magnetosphere [Liang et al, 2010[Liang et al, , 2011Ni et al, 2011cNi et al, , 2014Zhang et al, 2014]. Recent studies suggest that diffuse auroras observed on the nightside are predominantly produced by the chorus waves in the inner (L < 8) magnetosphere and by the ECH waves in the outer (L > 8) magnetosphere [Liang et al, 2010[Liang et al, , 2011Ni et al, 2011cNi et al, , 2014Zhang et al, 2014].…”
Section: Dayside Diffuse Aurora and Ech Wavesmentioning
confidence: 99%
“…Discrete auroras are characterized by intense luminosity in various auroral forms, such as arcs, bands, curls, and rays, and those observed near magnetic local noon (MLN) are caused by particles from the magnetosheath and are on the open field lines [Lockwood, 1997;Mende et al, 2016]. Diffuse auroras, appearing as relatively homogenous and weak emissions in green line (wavelength of 557.7 nm) auroral observations, are found on the equatorward edge of the auroral oval [Lui et al, 1973] and are caused by scattering the electrons from the central plasma sheet (CPS) [Meng et al, 1979] by whistler mode chorus [Ni et al, 2011a;Nishimura et al, 2010;Thorne et al, 2010] or electron cyclotron harmonic (ECH) [Horne and Thorne, 2000;Liang et al, 2011;Ni et al, 2011b;Zhang et al, 2014] waves. The diffuse auroras are strongest on the postmidnight sector [Newell et al, 2009] and also can be observed on the dayside [Newell and Meng, 1992;Sandholt et al, 1998].…”
Section: Introductionmentioning
confidence: 99%